GAYA KEPEMIMPINAN YANG MELAYANI DAN KUALITAS KEHIDUPAN KERJA SEBAGAI PREDIKTOR PERILAKU KEWARGAAN ORGANISASI - , Bethya Paramita, IJK. Sito Meiyanto, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
External environment of the organization that keeps changing needs optimum performance from all of the members of the organization. This is for the sake of effectiveness in the organization through organizational citizenship behavior. The purpose of this research is to test the right model from predictors combination of servant leadership style and quality of working life toward organizational citizenship behavior. The assessment is done by using scales. The scale of servant leadership style is adapted from assessment instrument by Barbuto and Wheeler (2006), the scale of quality of working life is adapted from assessment instrument by Lee, Singhapakdi, and Sirgy (2007), and the scale of organizational citizenship behavior is adapted from assessment instrument by Podsakoff, MacKenzie, Moorman, and Fetter (1990). The subjects in this research amounted to 83 people who works at PT X. The result of the analysis of multiple regression shows that servant leadership style and quality of working life altogether have correlation with organizational citizenship behavior with F value=7.130, p=0.001, and R2=0.151. Quality of working life can be the predictor of organizational citizenship behavior with effective contribution value 8.22%. But then, servant leadership style is not significant to be a predictor of organizational citizenship behavior